Impact of Preventive Measures upon Children’s Emotional Behaviors during COVID-19 Pandemic in Mosul City - Sinan Samer Ahmed, Mscn, Eqbal Ghanian Ali Ma’ala, Phd (Pakistan Journal of Medical & Health Sciences, 2022)
The study aimed to evaluate children’s emotional behaviors during COVID-19 pandemic in Mosul city and to find out the relationship between children behavior and their socio-demographic characteristics. A quantitative research (descriptive study design) was carried out from the 11th of May until the 2nd of November 2021. A non-probability (Purposive) sample technique is chosen for the current study. The sample involved of (620) children selected from the pediatric consultation clinics in the three of Mosul Hospitals. Scale was used called strengths and difficulties questionnaire (SDQ) for children behavioral screening. The data analyzed by the use of both descriptive and inferential statistical analysis procedures by SPSS version 26. The results of the study reflects abnormal emotional behavior represent by highest percentage (79.4%), and then this percentage was followed by (19.5%) with normal behaviors, while represent (1.1%) by borderline,. children emotional behavior shows that is more affected by preventive measures (lockdown and social separation) during the COVID-19 pandemic outbreak. The result of the present study revealed that is only a high significant association between children emotional behaviors with their gender of child’s (0.015) and residence (0.000) at P. value ≤ 0.05 levels. The study concluded that there is a clear impact upon children’s behavior due to the preventive measures (lockdown and social separation) that were imposed due to the COVID-19 pandemic. Emotional behavior is more affected than other types of behaviors. Child’s gender and residence of living shows high significant effects with total difficult score of behaviors. The study recommendation the following: detecting on children who have abnormal behavior and refer the suspected cases of having behavioral problems to psychological counseling clinics, that’s because a long-term of disorderly behavior leads to mental disorders and may accompany children at puberty. Work on developing plans and programs for entertainment and dealing with children during the home confinement in the future when other pandemics occur or recurrent. Establishing psychiatric medical and Nursing consultations for children by communication with parents, or allocating a phone number for this purpose in the event of a lockdown when parents notice any changes in children behavior.